Immunitet państwa, ius cogens a ochrona dziedzictwa kultury – uwagi krytyczne w świetle wyroku MTS z dnia 3 lutego 2012 r. w sprawie Niemcy v. Włochy - Jakubowski, Andrzej (Kwartalnik Prawa Publicznego, 2012)
This paper explores to what extent the evolution of international legal norms on jurisdictional immunity of states in relation to grave violation of humanitarian law and jus cogens may affect the regime on immunity from execution and measures of constraint enjoyed by state cultural property abroad. This topic is particularly timing due to the recent attempts of the victims of war and terrorist crimes to seek redress against the cultural property owned by states responsible for such grave violations of international law. Recalling the 2012 ICJ judgment in Jurisdictional immunity of the State Case (Germany v Italy), the paper aims at analyzing the current state of international law with regard to immunity of states and their cultural property. It argues that nowadays the immunity from execution and measures of constraint in respect of state cultural property experiences a stage of consolidation or even certain withdrawal from most progressive restrictive theories. However, this tendency is not driven by the reinforcement of the principle of sovereign equality of states, but it is rather drawn from the universally recognized assumption that the property forming part of the cultural heritage of a state shall be spared from the reach of such judicial measures, due to the protected and commonly shared interests and values.